2022
DOI: 10.3171/2021.10.focus21514
|View full text |Cite
|
Sign up to set email alerts
|

Robot-guided versus freehand fluoroscopy-guided minimally invasive transforaminal lumbar interbody fusion: a single-institution, observational, case-control study

Abstract: OBJECTIVE The use of robotics in spinal surgery has gained popularity because of its promising accuracy and safety. ROSA is a commonly used surgical robot system for spinal surgery. The aim of this study was to compare outcomes between robot-guided and freehand fluoroscopy-guided instrumentation in minimally invasive surgery (MIS)–transforaminal lumbar interbody fusion (TLIF). METHODS This retrospective consecutive series reviewed 224 patients who underwent MIS-TLIF from March 2019 to April 2020 at a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A nal 21 articles met the inclusion criteria for quantitative analysis. Among them, there were 2 randomized controlled trials (RCTs) [27,29] and 19 observational studies (cohort study) [8,[18][19][20][21][22][23][24][25][26]28,[30][31][32][33][34][35][36][37] . Characteristics of included studies as well as quality assessments are summarized in Table 2, Table 3, and Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A nal 21 articles met the inclusion criteria for quantitative analysis. Among them, there were 2 randomized controlled trials (RCTs) [27,29] and 19 observational studies (cohort study) [8,[18][19][20][21][22][23][24][25][26]28,[30][31][32][33][34][35][36][37] . Characteristics of included studies as well as quality assessments are summarized in Table 2, Table 3, and Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no evidence suggesting that RA TLIF can reduce surgical time and intraoperative blood loss. The results of this meta-analysis revealed that there was no signi cant difference in surgical time between the two groups [8,18,[20][21][22][23][24][25][26]28,30,[32][33][34][35][36][37] , and the funnel plot remained unchanged after applying the trim-and-ll method, indicating result stability. However, when combining the results of RCTs [27,29] , it showed that RA had a shorter surgical time compared to the FG group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experience of Cui et al [ 91 ] with robotic-assisted pedicle screw placement in 23 MIS-TLIF patients revealed significant favorability in pedicle screw accuracy, intraoperative blood loss, postoperative pain, postoperative drainage, recovery time, and paraspinal muscle atrophy relative to 25 open TLIF patients. Lin et al [ 92 ] compared 75 MIS-TLIF patients who underwent robotic-assisted pedicle screw fixation to 149 patients receiving freehand fluoroscopy-assisted fixation, noting similar postoperative outcomes between cohorts, with robotic-assisted patients experiencing significantly reduced blood loss, as well as reduced operative time for procedures on more than 3 vertebral levels. Vo et al [ 93 ] recently commented on the current state of robotic applications in spine surgery, indicating that robotics are most highly investigated in the capacity of instrumentation guidance.…”
Section: Looking Ahead: Continued Evolution Of the Mis-tlifmentioning
confidence: 99%